(untitled) (Sebha University Conference Proceedings, 2025)
The main aim of this paper is to evaluate existing steel structure building through the safety of bolts at connections, the steel structure is checked by designer through safety of elements due to structure analysis, and safety of foundations but not through safety of bolts, so that this study becomes important to check the safety through bolts at connections, specially it’s noted that there is corrosion at bolts and some bolts are not tightened well. A total of 70 samples have taken, from beam to column connections for each floor, and from beam to beam connections for each floor too, and from different size of bolts (16 mm, 20 mm, and 24 mm) all bolts taken were from Grade 5.6. All samples were tested under tensile at Istanbul Technical University. Results show that all bolts in good strength, it is higher than specifications of Grade 5.6 in yield stress with 81 % and in tensile strength with 27 % , the results show that bolts are from Grade 6.8 according to bolts standard, so it is recommended that bolts do not need to replace in this existing building, and they only need tightening wherever needed, and results may interpreted that during the construction period of the building (1980s) manufacture used written lesser Grade on bolts as safety factor.